Bioethanol production from sago starch - Mel, Maizirwan; Muhammad Nadzri, Husna; Kamarudin, Mohd Hider; Abd Karim, Mohd Ismail (2010)
Two stage processes prior to ethanol production has been proposed which is hydrolysis and fermentation. Commercial enzymes were used in this two steps hydrolysis; α-amylase (liquefaction step) and glucoamylase (saccharification step). Optimization was carried out in both stages; hydrolysis and fermentation. Three parameters are involved in optimization of % dextrose equivalent (DE); sago starch concentration (20% (w/v), 30% (w/v), 40% (w/v)), glucoamylase enzyme (52 U/g, 78 U/g, 104 U/g) and time during saccharification (1, 2, 3 hours). Three parameters are involved in optimization of ethanol; agitation (100 rpm, 150 rpm, 200 rpm), inoculums (1% (v/v), 3% (v/v), 5% (v/v)) from constant initial stock of 2.5x106 cells/mL and pH (4, 5, 6). Both optimization studies were carried out using Box-Behnken design. The experiment showed that the optimum parameters for hydrolysis study was identified to be glucoamylase (75.87 U/g), substrate concentration (28.49% (w/v)), and time (2 hours) which produced 62.15 g/L glucose as the fermentation substrate. For ethanol fermentation study, it was identified that the optimum parameters that produced 29.25 g/L were 167 rpm agitation, 3.43% (v/v) inoculums and pH 5.